Application Plan Sample Based on Professional Values Model in Pediatric Nurses - Ayla Kaya; Ayşegül İşler Dalgıç (Association of Nurse Managers, 2020)
Nursing models are guides in nursing education, research, practice and management by providing a professional language. This application plan sample prepared for pediatric nurses is based on Professional Values Model. It is thought that it is important to take professional values as a guide for pediatric nurses to take care of the interests of the individuals they care for, to support family-centered care practices and to make the right decisions in the ethical dilemmas. In conducting interventional studies for the development of professional values of pediatric nurses, it may be recommended to take a sample of the application plan presented in this study.